What is a feminist exhibition? Considering Contemporary Australia: Women. Issue 2 (2nd April 2016) - Best, Susan
ABSTRACT: This article evaluates the 2012 exhibition Contemporary Australia: Women held at the Gallery of Modern Art in Brisbane. It considers the criticisms of the exhibition and situates the show in relation to the international trend called the "feminist blockbuster" by Hilary Robinson.